PENGARUH BEBERAPA BAHAN AKTIF HERBISIDA PADA SISTEM TANAM SEGITIGA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays var.saccharata Sturt.) - Riski Primonta Ginting; Syafrinal Syafrinal; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to find out the effects of herbicides types used in weed control against sweet corn growth and production on a triangular planting system. The experiment has been conducted at the Experimental Farm of the Faculty of Agriculture, Riau University, Soil Laboratory agricultural faculty, and Botani Laboratory FMIPA Riau University from December 2016 to March 2017. The experimental unit was arranged in a Completely Randomized Design, consisting of 4 treatments and 5 replications. The treatments consisted of the without herbicides, herbicides isopropil amina glifosat, paraquat diclorida and mesotrion + atrazine. The Observed parameter are planth height, girth diameter, chlorofil content, male and female flower appearance time, cob weight without cornhusk per plant, cob yield cornhusk per plot, number of seed rows, cob diameter, cob length, weed plant biomass and vegetation analysis before and after treatment. The data acquaired from analysis of variance were tested with Duncan’s multiple range test at 5% level. Research result shows that Mesotrion + Atrazine treatments is better in raising sweet corn yield component. Key words : Herbicide, triangular planting system, sweet corn